P03.09 Implementing sexual health 'spaced education' for undergraduate medical students in new south wales, australia. (13th September 2015) - Bonner, M; Bourne, C; Rhee, J; Robinson, F; Tam, M
Abstract : Introduction: Most STIs are managed in primary care settings in Australia, so the New South Wales (NSW) STI Programs Unit supports sexual health education of professionals in these settings. However each NSW undergraduate medical school curriculum is different and is inconsistently taught. To support some consistency in teaching, the Workforce Education Development Group (WEDG) University of Sydney (USyd) agreed to develop and implement a sexual health module for medical students using spaced education (Qstream). Spaced education has been shown to improve knowledge acquisition, increase long-term knowledge retention and change behaviour. Methods: The University of NSW and USyd Medical School Academic Departments of General Practice agreed to pilot the module during undergraduate primary care clinical attachments. Sixteen clinical scenarios with questions, model answers, references, and links to key resources were developed. Results: Forty two undergraduate medical students completed the pilot providing mostly positive feedback about the delivery method (interactive, daily reminders, retesting knowledge) and content (realistic clinical scenarios). The main criticism was the desire for more case studies to compliment or fill gaps in prior learning. The sexual health module is now offered during 5 th and 6 th year Primary Care attachments at UNSW and is a required learning activity during 3 rd year Community Health block at USyd. From August 2014–March 2015, 88 students from UNSW have commenced the course with a 50% completion rate. From October – December 2014, all 61 medical students at USyd completed the course with 64% finding the course very helpful or helpful. Feedback since module implementation remains positive with mobile friendliness, reminders, gradual learning and scenario rationales all rated highly. Conclusion: Spaced education has proven adaptable to sexual health education and was accepted as beneficial and a positive style of learning about sexual health. Other NSW undergraduate programs have now been offered the module. Disclosure of interest statement: The NSW STI Programs Unit is funded by NSW Health. No pharmaceutical grants were received in the development of this project.